A penalty approach to obtain lower bound buckling loads of imperfection-sensitive shells - Godoy, Luis A.; Jaca, Rossana C.; Sosa, Eduardo M.; Flores, Fernando G. (2024)
Fil: Godoy, Luis A. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.